Penafsiran Ayat Ayat Tentang Istiqomah - Miftahul Diyanah; Selvi Yeni Safitri (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Istiqomah is a foundational concept in Islam that symbolizes firmness, consistency, and stability in implementing religious teachings. In the Qur'an, there are several verses that emphasize the importance of istiqomah, including Surah At-Tawbah verse 7, Surah Al-Fussilat verse 30, Surah Al-Ahqaf verse 13, and Surah Al-Jin verse 16. This study aims to analyze the interpretation of verses about istiqomah through the views of classical and contemporary mufassirs, such as Ibn Kathir. To understand its implications in the life of a Muslim. The results of the study show that istiqomah is not only related to faith in Allah, but also includes aspects of worship and morals. Istiqomah in faith means remaining firm in monotheism and avoiding shirk. In the aspect of worship, istiqomah is realized through consistency in carrying out religious obligations, such as prayer, fasting, and other righteous deeds. While in the aspect of morals, istiqomah means maintaining good values and resilience in the face of life's tests and trials. Furthermore, the interpretation of istiqomah verses also shows that people who are consistent in istiqomah will achieve peace of mind, protection from fear and sadness, and happiness both in this world and the hereafter. The conclusion of this study is that istiqomah is the key for a Muslim to achieve the blessing of life and achieve the pleasure of Allah SWT. Therefore, istiqomah should be an integral part of a Muslim's life principles in all aspects of life.